A study of biochemical and morphological aspects of macrophage function in experimental murine Nocardia asteroides and Nocardia brasiliensis infections - Stephens, Janet (Division of Clinical Pharmacology, 2018)
It is submitted in this thesis that the degree of activation or inhibition of macrophage function may differ in N. asteroides and N. brasiliensis infections with respect to release of plasminogen activator and of lysozyme The pattern of secretion of plasminogen activator and lysozyme in N. asteroides infections appears to differ in N. brasiliensis infection; and there is possibly a difference in the amount of lysozyme released by 2 day N. asteroides-activated macrophages and 2 day N. brasiliensis -activated macrophages. Strains of Nocardia organism did not influence macrophage morphology or ultrastructure. The study also shows the biochemical characteristics of plasminogen activator and lysozyme release, but not macrophage morphology and ultrastructure, are modified in the first 21 days of experimental Nocardia infections. There are three apparent mechanisms by which virulent strains of N. asteroides manage to survive within macrophages: (i) an ability to inhibit phagosome-lysozome fusion: (ii) alteration in the intraphagosomal pH: and (iii) alteration in the activity of the lysozomal enzyme acid-phosphatase. This study attempted to elucidate further the mechanisms enabling Nocardia organisms to persist and grow within macrophages. Reduced lysozyme release reflects diminished functional status of the macrophages of mice inoculated with N. asteroides or N. brasiliensis at certain times during infection. Reduced intracellular lysozyme levels have been linked with defects in bactericidal function. Such a reduction in intracellular and consequently extracellular levels of lysozyme might explain the capacity of Nocardia to survive intracellularly and to proliferate in the macrophage host.